2020
DOI: 10.1186/s13024-020-00368-6
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and propagation of α-synuclein aggregation in the nervous system

Abstract: The two main pathological hallmarks of Parkinson's disease are loss of dopamine neurons in the substantia nigra pars compacta and proteinaceous amyloid fibrils composed mostly of α-synuclein, called Lewy pathology. Levodopa to enhance dopaminergic transmission remains one of the most effective treatment for alleviating the motor symptoms of Parkinson's disease (Olanow, Mov Disord 34:812-815, 2019). In addition, deep brain stimulation (Bronstein et al., Arch Neurol 68:165, 2011) to modulate basal ganglia circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 146 publications
(164 reference statements)
6
150
0
1
Order By: Relevance
“…Lewy bodies contain aggregated α-synuclein as a main component, as well as a number of other proteins and lipid membrane fragments. Aggregation of misfolded α-synuclein can impair axonal transport and proteostasis, leading to degeneration of neurites and cell death [22,23].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Lewy bodies contain aggregated α-synuclein as a main component, as well as a number of other proteins and lipid membrane fragments. Aggregation of misfolded α-synuclein can impair axonal transport and proteostasis, leading to degeneration of neurites and cell death [22,23].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Normally, α-synuclein is encoded by multiple genes on the autosome and is responsible for regulating dopamine metabolism. When this gene is mutated, it can cause the pathological accumulation of α-synuclein to form Lewy bodies and stimulate neuronal degeneration [ 124 , 125 , 126 , 127 ]. In addition to genetic mutations of α-synuclein gene, increased post-translational modifications of this protein under elevated oxidative stress in PD could result in the accumulation and/or aggregation of its oligomers [ 120 ].…”
Section: Autophagy and Nddsmentioning
confidence: 99%
“…It was shown that α-synuclein is degraded by chaperone-mediated autophagy (CMA) and macroautophagy pathways, where CMA is the main mechanism [ 129 , 130 ]. However, mutated α-synuclein leads to its decreased binding to chaperone protein molecules in CMA, leading to the formation of Lewy bodies [ 124 , 126 ]. Some cases of familial PD were related to the repeated expression of the α-synuclein gene.…”
Section: Autophagy and Nddsmentioning
confidence: 99%
“…In addition to AD, MT dysfunction has been considered an important contributor also to the pathogenesis of Parkinson’s disease (PD), a neurodegenerative condition characterized by the loss of dopaminergic neurons from substantia nigra and the presence in these cells of intracellular inclusions of α-synuclein (α-syn) [ 266 ].…”
Section: Microtubule Dysfunction and Neurodegenerationmentioning
confidence: 99%